Aging, cell senescence, the pathogenesis and targeted therapies of intervertebral disc degeneration - Xu, Jiongnan; Shao, Ting; Lou, Jianfen; Zhang, Jun; Xia, Chen (Frontiers in Pharmacology, 2023)
Intervertebral disc degeneration (IVDD) refers to the aging and degenerative diseases of intervertebral disc components such as nucleus pulposus, annulus fibrosus, and cartilage endplate, and is the main cause of chronic low back pain. Over the past few years, many researchers around the world concerned that the degeneration of nucleus pulposus (NP) cells plays the main role in IVDD. The degeneration of NP cells is caused by a series of pathological processes, including oxidative stress, inflammatory response, apoptosis, abnormal proliferation, and autophagy. Interestingly, many studies have found a close relationship between the senescence of NP cells and the progression of NP degeneration. The classical aging pathways also have been confirmed to be involved in the pathological process of IVDD. Moreover, several anti-aging drugs have been used to treat IVDD by inhibiting NP cells senescence, such as proanthocyanidins, resveratrol and bone morphogenetic protein 2. Therefore, this article will systematically list and discuss aging, cell senescence, the pathogenesis and targeted therapies of IVDD, in order to provide new ideas for the treatment of IVDD in the future.